Loss Aversion and Inefficient Renegotiation - Klaus Schmidt; Fabian Herweg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We propose a theory of inefficient renegotiation that is based on loss aversion. When two parties write a long-term contract that has to be renegoti- ated after the realization of the state of the world, they take the initial contract as a reference point to which they compare gains and losses of the renegotiated transaction. We show that loss aversion makes the renegotiated outcome sticky and materially inefficient. The theory has important implications for the optimal design of long-term contracts. First, it explains why parties often abstain from writing a beneficial long-term contract or why some contracts specify transactions that are never ex post efficient. Second, it shows under what conditions parties should rely on the allocation of ownership rights to protect relationship-specific investments rather than writing a specific performance contract. Third, it shows that employment contracts can be strictly optimal even if parties are free to rene- gotiate.
Keywords: C78; D03; D86; 330